Noninvasive Characterization of Human Glymphatics and Meningeal Lymphatics in an in vivo Model of Blood–Brain Barrier Leakage. Issue 1 (23rd October 2020) - Wu, Chia‐Hung; Lirng, Jiing‐Feng; Ling, Yu‐Hsiang; Wang, Yen‐Feng; Wu, Hsiu‐Mei; Fuh, Jong‐Ling; Lin, Po‐Chen; Wang, Shuu‐Jiun; Chen, Shih‐Pin
Abstract : Objective: To evaluate human glymphatics and meningeal lymphatics noninvasively. Methods: This prospective study implemented 3‐dimensional (3D) isotropic contrast‐enhanced T2 fluid‐attenuated inversion recovery (CE‐T2‐FLAIR) imaging with a 3T magnetic resonance machine to study cerebral glymphatics and meningeal lymphatics in patients with reversible cerebral vasoconstriction syndrome (RCVS) with (n = 92) or without (n = 90) blood–brain barrier (BBB) disruption and a diseased control group with cluster headache (n = 35). The contrast agent gadobutrol (0.2mmol/kg [0.2ml/kg]) was administered intravenously in all study subjects. Results: In total, 217 patients (182 RCVS, 35 cluster headache) were analyzed and separated into 2 groups based on the presence or absence of visible gadolinium (Gd) leakage. Para‐arterial tracer enrichment was clearly depicted in those with overt BBB disruption, while paravenous and parasinus meningeal contrast enrichment was evident in both groups. Paravenous and parasinus contrast enrichment remained in RCVS patients in the remission stage and in cluster headache patients, suggesting that these meningeal lymphatic channels were universal anatomical structures rather than being phase‐ or condition‐specific. Additionally, we demonstrated nodular leptomeningeal enhancement in 32.3% of participants, which might represent potential lymphatic reservoirs. Four selected RCVS patients who received consecutive contrasted 3D isotropic FLAIR imaging after gadobutrol administration showed that the Gd persisted for at least 54 minutes and was completely cleared within 18 hours. Interpretation: This large‐scale in vivo study successfully demonstrated the putative human para‐arterial glymphatic transports and meningeal lymphatics by clear depiction of para‐arterial, parasinus, and paravenous meningeal contrast enrichment using high‐resolution 3D isotropic CE‐T2‐FLAIR imaging noninvasively; this technique may serve as a basis for further studies to delineate clinical relevance of glymphatic clearance. ANN NEUROL 2021;89:111–124